Deferoxamine Treatment Combined With Sevoflurane Postconditioning Attenuates Myocardial Ischemia-Reperfusion Injury by Restoring HIF-1/BNIP3-Mediated Mitochondrial Autophagy in GK Rats - Yang, Long; Xie, Peng; Wu, Jianjiang; Yu, Jin; Li, Xin; Ma, Haiping; Yu, Tian; Wang, Haiying; Ye, Jianrong; Wang, Jiang; Zheng, Hong (Frontiers in Pharmacology, 2020)
Mitochondrial autophagy is involved in myocardial protection of sevoflurane postconditioning (SPostC) and in diabetic state this protective effect is weakened due to impaired HIF-1 signaling pathway. Previous studies have proved that deferoxamine (DFO) could activate impaired HIF-1α in diabetic state to restore the cardioprotective of sevoflurane, while the specific mechanism is unclear. This study aims to investigate whether HIF-1 /BNIP3-mediated mitochondrial autophagy is involved in the restoration of sevoflurane postconditioning cardioprotection in diabetic state. Ischemia/reperfusion （I/R）model was established by ligating the anterior descending coronary artery and sevoflurane was administered at the first 15 minutes of reperfusion. Myocardial infarct size, mitochondrial ultrastructure and autophagosome, ATP content, mitochondrial membrane potential, ROS production, HIF-1α, BNIP3, LC3B-II, Beclin-1, P62, LAMP2 protein expression were detected 2h after reperfusion, and cardiac function was evaluated by ultrasound at 24h after reperfusion.Our results showed that with DFO treatment, SPostC up-regulated the expression of HIF-1α and BNIP3, thus reduced the expression of key autophagy proteins LC3B-II, Beclin-1,p62 and increased the expression of LAMP2. Furthermore, it reduced the accumulation of autophagosomes and ROS production, increased the content of ATP, and stabilized the membrane potential. Finally, the myocardial infarction size was reduced and cardiac function was improved. Taken together, DFO treatment combined with SPostC could alleviate myocardial ischemia reperfusion injury in diabetic rats by restoring and promoting HIF-1 / BNIP3-mediated mitochondrial autophagy.